2016
DOI: 10.1007/s12310-016-9201-4
|View full text |Cite
|
Sign up to set email alerts
|

High School Teachers’ Openness to Adopting New Practices: The Role of Personal Resources and Organizational Climate

Abstract: Although evidence-based practices for students’ social, emotional, and behavioral health are readily available, their adoption and quality implementation in schools are of increasing concern. Teachers are vital to implementation; yet, there is limited research on teachers’ openness to adopting new practices, which may be essential to successful program adoption and implementation. The current study explored how perceptions of principal support, teacher affiliation, teacher efficacy, and burnout relate to teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 58 publications
3
32
0
Order By: Relevance
“…The research on attitudes on EBPs implementation in education is not as extensive as in other fields (e.g. health care and business) (Johnson et al, 2017), and we have not fully understood how the decision to adopt EBPs is influenced by teacher attitudes (Monahan et al, 2014). Additionally, to the author's knowledge, the association between EBPs adoption and teacher attitudes towards EBPs in the context of early childhood social outcomes has not been examined systematically by previous studies.…”
Section: Contextualising the Role Of Teacher Attitudes In The Implementation Of Evidence-based Practices For Early Childhood Social Learnmentioning
confidence: 99%
“…The research on attitudes on EBPs implementation in education is not as extensive as in other fields (e.g. health care and business) (Johnson et al, 2017), and we have not fully understood how the decision to adopt EBPs is influenced by teacher attitudes (Monahan et al, 2014). Additionally, to the author's knowledge, the association between EBPs adoption and teacher attitudes towards EBPs in the context of early childhood social outcomes has not been examined systematically by previous studies.…”
Section: Contextualising the Role Of Teacher Attitudes In The Implementation Of Evidence-based Practices For Early Childhood Social Learnmentioning
confidence: 99%
“…As a result, this training leads to qualitative changes of teacher's personal potential providing a variety of professional perspective, the ability to the destruction of stereotypes and to the formation of new innovation attitudes. Similar questions were discussed by Johnson, Pas, Loh, Debnam, and Bradshaw (2017). Also questions about collaborative work and demands of usage innovative methods of learning management are discussed by Baleghi-Zadeh, Ayub, Mahmud, and Daud (2017), Budiardjo, Pamenan, Hidayanto, Meyliana, and Cofriyanti (2017) and Hao, Barnes, Branch, and Wright (2017).…”
Section: Discussionmentioning
confidence: 85%
“…This may be because of differences between the structure of elementary and middle school environments (e.g., in middle school, the teacher likely only has the student for class once [or less] a day, meaning there is less time to make up content [a dosage factor] across the day). In addition to a supportive climate, in one of the few studies looking at non-elementary programming, Johnson et al (2017) found that greater principal support was associated with greater openness to adopt new SEL practices among high school teachers in Maryland, and qualitative work by Barwick, Barac, Akrong, Johnson, and Chaban (2014) also found that a key motivator for practice change among Canadian educators included organizational support for implementation, such as administrator buy-in. Thus, organizational climate may function in multiple ways in the school setting and is deserving of additional study.…”
Section: Discussionmentioning
confidence: 99%
“…Gregory, Henry, Schoeny, and The Metropolitan Area Child Study Research Group (2007) also found that more supportive perceived school climate was associated with dosage of violence prevention programming in a sample of teachers from 10 elementary and two middle schools in Chicago and adjoining area. A solid body of research also identifies the importance of perceived principal support to universal program implementation quality (e.g., Johnson, Pas, Loh, Debnam, & Bradshaw, 2017; Ringwalt et al, 2003); in the larger mental health services field, leadership qualities have also been demonstrated as key to promoting a positive implementation climate (i.e., a shared understanding of the types of practices and behaviors that are rewarded, supported, and expected in the organization; Aarons, Ehrhart, Farahnak, & Sklar, 2013) and positive provider attitudes about program adoption (Aarons, 2006). In the Canadian context, however, work in the school setting has primarily focused on the implementation of positive behavior interventions at the elementary level (Kelm, McIntosh, & Cooley, 2014; McIntosh, Moniz, Craft, Golby, & Steinwand-Deschambeault, 2014).…”
Section: Introductionmentioning
confidence: 99%